Material properties of the cyanobacterial reserve polymer multi-l-arginyl-poly-l-aspartate (cyanophycin). (27th January 2017) - Khlystov, Nikita A.; Chan, Wui Yarn; Kunjapur, Aditya M.; Shi, Weichao; Prather, Kristala L.J.; Olsen, Bradley D.
Abstract: Bio-sourced macromolecules such as cyanophycin are an attractive source for alternative, sustainable plastics. While the chemical structure and biological function of cyanophycin have been previously investigated, its material properties remain largely unexplored. This study investigates the structural, thermal, mechanical, and solution properties of cyanophycin produced from recombinant Escherichia coli . Unplasticized, it has an elastic compression modulus of about 560 MPa and undergoes brittle failure at 78 MPa. Cyanophycin exhibits thermal stability in air up to 200 °C and does not undergo glass transition within its limit of thermal stability. The polypeptide is amorphous and has no long-range ordering in the solid state. In solution, water-soluble cyanophycin is thermoresponsive, exhibiting both upper and lower critical solution temperatures. Because the feasibility of industrial scale cyanophycin production through fermentation has been well studied, an expanded understanding of its materials properties should contribute to the development of new applications for this biopolymer. Graphical abstract: Highlights: Material properties of water-soluble recombinant cyanophycin are studied. Cyanophycin is a brittle, amorphous material with good thermal stability. Zwitterionic character of cyanophycin leads to salt dependent LCST and UCST behavior.